Menumbuhkan semangat berprestasi melalui achievement motivation training bagi pedagang pengecer - Fisla Wirda; Trimardi Jaya Putra; Wilson Gustiawan (ABDIMAS DEWANTARA, 2023)
Management is a determining factor for business success, both human resources management, marketing, or finance. One of the problems in Human Resource Management for traders is the low achievement to improve business performance. This activity aims to increase achievement motivation for retailers. This training lasted for three days and was attended by 50 retailers with the following topics: Becoming a Successful Entrepreneur, Knowing Entrepreneurial Character, and Marketing. The training participants were very enthusiastic about participating in all training activities in the form of lectures, games, discussions, and simulations. This activity was successful, as indicated by the low level of absenteeism training and participants' absorption of the material. Participants were satisfied with the materials, methods, and trainers provided during the training. Retailers are enthusiastic about training activities because the opportunities for participating are very limited. This activity is useful in increasing the knowledge and motivation of retailers.   Abstrak: Manajemen usaha merupakan faktor penentu keberhasilan usaha, baik manajemen Sumber Daya Manusia, pemasaran ataupun keuangan. Salah satu permasalahan dibidang Manajemen Sumber Daya Manusia bagi pedagang pengecer adalah rendahnya semangat berprestasi sehingga keinginan untuk meningkatkan kinerja usaha rendah. Kegiatan ini bertujuan untuk meningkatkan motivasi berprestasi/achievement motivation  pedagang pengecer. Pelatihan ini berlangsung selama 3 hari yang diikuti oleh 50 pedagang pengecer  dengan materi:  Menjadi Wirausaha yang Sukses, Mengenal Karakter Wirausaha dan  Marketing. Peserta sangat antusias mengikuti semua kegiatan pelatihan baik yang berbentuk ceramah, games, diskusi dan simulasi. Kegiatan pelatihan ini berhasil dengan baik yang dibuktikan dengan  rendahnya tingkat absensi peserta dan tingginya daya serap peserta terhadap materi pelatihan. Peserta puas dengan materi, metoda dan trainer yang disediakan selama pelatihan. Pedagang pengecer antusias dalam kegiatan pelatihan  karena kesempatan mengikuti pelatihan yang sangat terbatas.  Kegiatan ini bermanfaat dalam menambah ilmu wawasan serta motivasi pedagang pengecer.